Assessment of central visual function after successful retinal detachment surgery by pattern visual evoked cortical potentials. Issue 8 (August 1992) - Ueda, M; Adachi-Usami, E
Abstract : The pattern of visual recovery after successful surgery by pattern visual evoked cortical potentials (VECP), visual acuity, colour vision, and critical fusion frequency was investigated in 14 eyes with retinal detachment involving the macula. The temporal tuning characteristics in the evoked potentials were measured as based on the P100 amplitude and the frequency necessary for evoking 0 mu V amplitude, which was defined as an objective critical fusion frequency by extrapolating the curve. Significant improvement in visual acuity and colour vision was observed within 2 months postoperatively. A significantly increased P100 peak latency became shorter as the postoperative days increased. In general, a good correlation was noted between the P100 peak latency and subjectively measured visual acuity, colour vision, and critical fusion frequency. The objective critical fusion frequency measured by VECP recovered gradually during the 6 months after surgery. Functional recovery was not related to the length of time the macula was detached before surgery.